PENGGUNAAN STRATEGI PEMBELAJARAN KONFLIK KOGNITIF DILENGKAPI HYPOTETHYCAL LEARNING TRAJECTORY PADA POKOK BAHASAN SUHU DAN KALOR DI SMA NEGERI 1 TANJUNG RAJA - Intan Megawati (JURNAL INOVASI DAN PEMBELAJARAN FISIKA, 2014)
This study aims Â to determine the learning trajectory on the temperature and head material Research method was chosen is design research. This research was conducted at SMA Negeri 1 Tanjung Raja by involving 6 student in the pilot experiment phase and 35 student in teaching experiment phase. This example from learning trajectory on activity 1, the first conflict question "whether the temperature and heat the same?" On this question, there is one track student learning, all groups of students were able to define the concept of temperature and heat properly. Then for the second conflict question The highest temperature of the container when dipped in the heated mass of different objects, there are two conflicting learning trajectory, the trajectory first consider if a container-mass objects are experiencing a higher temperature rise, whereas the second study considers the trajectory if a container body of mass great is that higher temperatures increase due to the larger mass objects can absorb more heat so that the heat given off is also much more so the higher the temperature of the container, this trajectory as expected researchers, to prove the answers students watch a video experiment conducted activity "samakah aku "and group discussions. After watching the video and discussion, then there is only one path to learn a second conflict on the question asked of teachers, all groups are expected to answer correctly according to researchers.